Exploring the relationship between restored ecosystem function and species composition: a meta-analysis - Forsythe,Katherine Jane (Percy FitzPatrick Institute of African Ornithology, 2014)
The idea that biodiversity confers higher levels of ecosystem functioning has been used as an argument for the conservation of biodiversity, and the relationship between these variables has been well researched. Ecosystem restoration often aims to restore former ecosystem functioning as well as specific species assemblages, not just biodiversity. In many cases monitoring programmes lack funds to measure all these aspects and often assume relationships between these variables; however, these relationships remain largely untested. In this thesis, I undertake the first ever meta-analysis of studies measuring ecological function and species composition in restored sites to test whether such a relationship exists. Bray-Curtis similarity measures were used to compare species composition for each site compared to multiple reference sites. Indicators of ecosystem function were also compared to reference sites, taking into account natural variation within reference sites. A weak relationship between ecosystem function and species composition was found, and it differed between different groups of ecosystem functions. Live plant biomass and structural framework ecosystem functions increased in similarity to reference sites as species composition also increased in similarity to reference sites. Nutrients, soil attributes and interactions between biotic component as well as litter and deadwood production, showed little association with species composition, with levels of ecosystem functioning showing little change as species composition became closer to reference sites. Variables relating to nutrients, soil attributes, and biotic interactions were always similar to intact sites regardless of the degree to which species composition had been restored. Live plant biomass, litter and deadwood production, and framework ecosystem functions, however, often did not reach reference levels of functioning, even when full species composition was restored. This analysis found that overall the shape of the relationship indicates redundancy in species composition, suggesting that increasing similarity in terms of species composition initially increases ecosystem function; however beyond a point, additional similarity does not further assist in the restoration of ecosystem function to reference levels of similarity. The main difference to biodiversity ecosystem function relationships comes with the fact that all ecosystem functions were not returned even when restored sites had similar species composition to reference sites, indicating that something, possibly time, is limiting the return of full ecosystem function to restoration sites. Finally, this research indicates that the relationship between species composition and ecosystem function is not consistent and it would be unwise to use species composition or ecosystem function as proxies for one another.